The Prevalence of Covid 19 in Third Trimester Pregnancy at Mayong II Jepara Community Health Centre Central Java 2021 - Nasriyah Nasriyah; Islami Islami; Nor Asiyah (International Journal of Health Science and Technology, 2021)
Covid-19 is a virus that spreads very quickly in the world community, including Indonesia. Incidence of Covid-19 is very high and the transmission is very fast so that it has become a pandemic in the world. Corona virus is characterized by several symptoms, such as fever, cough and shortness of breath. In severe conditions, this viral infection can cause acute respiratory failure, severe pneumonia (lung infection), pulmonary edema, failure of body organs, and even death. The incidence of Covid-19 infection in pregnancy is increasing, therefore pregnant women are extra careful in maintaining their pregnancy. This study aims to determine the prevalence of third trimester in pregnant women who confirmed by Covid-19 at the Mayong II Jepara Community Health Center. The research method used a descriptive study with a population of all pregnant women who were examined at the Mayong II Jepara Community Health Center in 2020. The research subjects were 80 respondent third trimester pregnant women during September-December 2020 by Polymerase Chain Reaction. The results showed that 80 respondents who carried out the PCR Swab, there were 7 respondents  an average age of 20-28 years who were confirmed as Covid-19. Based on the results of this study, it is necessary for pregnant women to continued to carry out health protocols. Pregnant women who are confirmed Covid-19 are expected to carry out self isolation and if severe symptoms arise, they should contact medical physician. As a medical physician, they were to monitor pregnant women who have confirmed Covid-19 and giving treatment quickly  in the event of complications related to pregnancy.